Relationship between climate change and agriculture at the EU level - Ivana Ilić; Sonja Jovanovic; Marija Petrović-Ranelović (Economic Themes, 2022)
The purpose of this study is investigating the homogeneity of the European Union countries (hereinafter: EU countries) according to the achieved level of environmental performance in agriculture and climate change in 2020. The data used for this study are from an internationally comparable database. For the purpose of validation of the laid hypothesis, methods of statistical analysis were employed. The study focuses on Climate change and Agriculture, two factors of the Ecosystem Vitality component, which will be considered in more detail, as well as the indicators included in the Environmental Performance Index (hereinafter: EPI) structure. The empirical findings revealed the existence of a medium and a positive quantitative agreement between the two environmental policy areas, agriculture and climate change. Also, the cluster analysis showed that most of the countries selected for the research apply agricultural production with controlled use of nitrogen, which further affects the reduced emissions of greenhouse gases and thus minimally contributes to climate change.
Keywords: Q15; Q54; O13; 330; agriculture; climate change impact; greenhouse gas emissions; adaptation; EPI; EU countries